Pemahaman Pendekatan Hadits Tekstual dan Konstekstual dalam Studi Hadist - Feriyanda Feriyanda; Ryan Syahputra (Universitas Muhammadiyah Enrekang, 2023)
ct. Textual and Contextual Approaches are very meaningful in terms of the science of hadith. Through this approach, it can be seen that this hadith did not appear just like that, but because of reasons and reasons. This textual approach is more directed towards Mahdah (Pure) charity through human contact with God or what is commonly called (Hablumminallah) with an example of prayer. Compared to the dominant Contextual in the historical, sociological in the cultural and temporal aspects of the hadith so that at times the understanding is not too standard but wiser through observing the modern situation in today's society without losing the spirit of the hadith texts.